Research and Analysis of the State and Development of Woody Plants in The Squares of the City of Krasnoyarsk. Issue 5 (March 2021) - Kuhar, I; Avdeeva, E
Abstract: The article presents the results of studies in different areas of the city of Krasnoyarsk with different levels of anthropogenic load and different levels of air pollution. An analysis was made of the stability of the development of woody plants in the squares of the city of Krasnoyarsk using the example of birch drooping according to two indicators: the asymmetry coefficient for five parameters of the leaves and the asymmetry value for the area of the leaves. The results of the study showed that technogenic impacts lead to a change in the size and magnitude of the fluctuating asymmetry of the drooping birch leaves. In the area with average extent of pollution decrease in stability of the development, being expressed in increase of values of indicators of asymmetry is noted. The greatest decrease in stability of development is noted in selection with a maximum level of pollution. According to the conducted researches, wood plants react to influence of an urban environment, thus methods of a dendroindikation are a theoretical basis of development of recommendations for an assessment of a condition of an urban environment.